Pengaruh Promo Flash Sale, Voucher Diskon Belanja, Dan Brand Image Pada E-Commerce Shopee Terhadap Perilaku Konsumtif Pada Masyarakat Di Kota Jambi Dalam Perspektif Ekonomi Islam - Fatima Azzahra; Rafiqi Rafiqi; Yusuf Zaini Aprizal (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of Flash Sale promotions, Shopping Discount Vouchers, and Brand Image on the consumptive behavior of Generation X in Shopee e-commerce in Jambi City from the perspective of Islamic Economics. The research employs a quantitative method with the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. Data were collected through questionnaires distributed to respondents categorized as Generation X in Jambi City. The results show that all three variables have a positive and significant effect, both partially and simultaneously, on consumptive behavior. Shopee’s digital marketing strategies effectively increase the consumptive tendencies of Generation X, who are generally known to be selective in shopping. From the Islamic Economics perspective, excessive consumptive behavior falls under israf (extravagance) and tabdzir (wastefulness), which contradict the principle of wasathiyah (moderation). Therefore, Muslim consumers should control their spending behavior by instilling the values of al-qana’ah (contentment) and al- iqtisad (simplicity), and direct their expenditures toward productive activities such as investment, saving, and ZISWAF (Zakat, Infaq, Sadaqah, and Waqf).